2019
DOI: 10.1016/j.gendis.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of congenital heart disease in down syndrome

Abstract: Down syndrome (DS), as a typical genomic aneuploidy, is a common cause of various birth defects, among which is congenital heart disease (CHD). 40–60% neonates with DS have some kinds of CHD. However, the molecular pathogenic mechanisms of DS associated CHD are still not fully understood. This review summarizes available studies on DS associated CHD from seven aspects so as to provide a crucial and updated overview of what we known so far in this domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 61 publications
(75 reference statements)
0
13
0
8
Order By: Relevance
“…Congenital heart defects have found in 40-60% of DS cases including 45% atrioventricular septal defects (AVSD) [5]. Rodrigues et al [6] reported that the frequency of CHD in dual DS-KS and DS populations seems to be different.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital heart defects have found in 40-60% of DS cases including 45% atrioventricular septal defects (AVSD) [5]. Rodrigues et al [6] reported that the frequency of CHD in dual DS-KS and DS populations seems to be different.…”
Section: Case Reportmentioning
confidence: 99%
“…Additionally, cardiac and gastrointestinal defects, hypothyroidism, and celiac disease are commonly associated with DS [3]. Congenital heart defects have found in 40-60% of DS cases [5] but rarely reported in children with KS [6]. This study aimed to report a fetus diagnosed with dual DS-KS who presents the characteristics of congenital heart defect.…”
Section: Introductionmentioning
confidence: 99%
“…CHD affects about 1% of live births and has become the leading cause of childhood mortality (2,3). Despite incomplete knowledge on the onset and development of CHD, recent findings indicate that intrauterine infection, environmental factors, chromosomal abnormalities, gene mutations and epigenetics are involved in this disease (4)(5)(6)(7). CHD phenotypes are diverse, involving pulmonary stenosis, aortic stenosis, atrial septal defect, aortic transposition, right ventricular double outlet, ventricular septal defect, patent ductus arteriosus, tetralogy of Fallot, and other types of defects (8).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that microRNAs on chromosome 21 (mir-nov21) are involved in the regulation of cardiac development by regulating the expression of GATA4 and other genes, while the inactivation of the GATA4 gene in the early stage of cardiac development can lead to cardiac hypoplasia and endocardial cushion defects, which may be one of the reasons for the frequent combination of CHD in patients with DS [8,9]. In addition, aberrations on chromosome 21 have also been con rmed to affect the fusion of endocardial cushions, leading to CHD [10]. Studies have shown that AVSD, ASD and VSD are the most common CHD types in children with DS [11].…”
Section: Introductionmentioning
confidence: 99%